COUNTRY-SPECIFIC ENVIRONMENTAL KUZNETS CURVES: A RANDOM COEFFICIENT APPROACH APPLIED TO HIGH-INCOME COUNTRIES - Figueroa, Eugenio (Estudios de Economía, 2016)
Cross-country estimations of the Environmental Kuznets Curve (EKC) to empiricallyanalyze the relationship between income and pollution have generallyassumed a common structure for all countries. Since this latter feature is notsupported by economic theory, this paper uses the Random Coefficient Modelproposed by Swamy (1970) and empirically estimates EKCs for sulfur dioxidewith specific turning points from a sample of 73 high and low income countries.A crucial aspect is that there are large differences between the estimated turningpoints of the EKCs for the different countries in the sample, which points tothe relevance of using the approach employed here since assuming a commonstructure for all countries erroneously hides this relevant empirical feature.Moreover, the analysis of the structure of the EKCs estimated suggests thatregulatory processes resembling market mechanisms could induce the empiricalemergence of EKCs. Finally, taking into consideration the most recent concernsin the literature, we econometrically checked, on the one hand, for the validity ofthe usual theoretical assumption of exogeneity of the per capita income variablein the EKC relationship and, on the other hand, for an eventual structural changecausing the sign change in the pollution-per capita income relationship of theEKC. The weak exogeneity and the structural break tests employed renderedplausible that income per capita is really the driver variable determining theEKC relationship found.